A phase-specific psychological therapy for people with problematic cannabis use following a first episode of psychosis: a randomized controlled trial. Issue 13 (October 2014) - Barrowclough, C.; Marshall, M.; Gregg, L.; Fitzsimmons, M.; Tomenson, B.; Warburton, J.; Lobban, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Cannabis use is high amongst young people who have recently had their first episode of psychosis, and is associated with worse outcomes. To date, interventions to reduce cannabis consumption have been largely ineffective, and it has been suggested that longer treatment periods are required. Method In a pragmatic single-blind randomized controlled trial 110 participants were randomly allocated to one of three conditions: a brief motivational interviewing and cognitive behavioural therapy (MI-CBT) intervention (up to 12 sessions over 4.5 months) with standard care from an early intervention service; a long MI-CBT intervention (up to 24 sessions over 9 months) with standard care; or standard care alone. The primary outcome was change in cannabis use as measured by Timeline Followback. Results Neither the extended nor the brief interventions conferred benefit over standard care in terms of reductions in frequency or amount of cannabis use. Also the interventions did not result in improvements in the assessed clinical outcomes, including symptoms, functioning, hospital admissions or relapse. Conclusions Integrated MI and CBT for people with cannabis use and recent-onset psychosis does not reduce cannabis use or improve clinical outcomes. These findings are consistent with those in the published literature, and additionally demonstrate that offering a more extended intervention does not confer any advantage. Many participants were not at an action stage for change and for those not ready to reduce or quit cannabis, targeting associated problems rather than the cannabis use per se may be the best current strategy for mental health services to adopt.